FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERAWATAN KELUARGA TERHADAP ORANG DENGAN GANGGUAN JIWA (ODGJ) - Aprilia Sapitri; Nurwijaya Fitri; Nova Mardiana; Indah Permata Sari (Citra Internasional Institute, 2024)
Family care is very important for people with mental disorders, because the family is the most important person to optimize mental peace for people with mental disorders. The aim of this research is to find out what factors are related to family care for people with mental disorders at the Regional Mental Hospital Polyclinic, Dr. Samsi Jacobalis Bangka Belitung Islands Province in 2024. This research is a quantitative study with a cross-sectional. The samples in this study were families of people with mental disorders who were recorded and registered as visiting the Polyclinic at the Regional Mental Hospital, dr. Samsi Jacobalis of Bangka Belitung Islands Province as many as 89 people. Data analysis used the chi square test with a confidence level of 95%. The results of this study concluded that the factors related to family care were education level (p=0.000), economic level (p=0.001), genetics (p=0.000) and the more dominant factor was knowledge (p=0.000 and POR=11.340). The conclusion in this study is that educational level, economic level, genetics and knowledge have a relationship with family care for people with mental disorders at the Regional Mental Hospital Polyclinic, Dr. Samsi Jacobalis Bangka Belitung Islands Province in 2024. The suggestion from this research is that it is hoped that the results of this research will be used as literature and reference to improve outreach and education in the community about the importance of family care for people with mental disorders, because ODGJ really need a helping hand and care.